N6-methyladenosine modification of FZR1 mRNA positively regulates antiviral innate immunity by targeting the MAVS–TRAF3/6 axis - Kaiwen Dou; Yiyi Hu; Mingyang Li; Jiale Xu; Weihao Zhang; Hui Wang; Qi Cheng; Zihao Jiang; Liangjun Chen; Shi Liu; Ke Chen; Yuanyuan Liu; et al. (Proceedings of the National Academy of Sciences, 2026)
Activation of retinoic acid-inducible gene-I-like receptors (RLRs) is important for type I interferon (IFN-I) production and antiviral innate immunity initiation. However, the epigenetic mechanisms that regulate RLR signaling remain poorly understood and require further investigation. Here, we demonstrate that Fizzy-related protein 1 (FZR1), which is essential for mitotic exit and G1/S transition, potentiates antiviral innate immune responses against RNA viruses. Mechanistically, vesicular stomatitis virus infection increases N6-methyladenosine (m 6 A) modification of FZR1 mRNA, which enhances FZR1 translation and elevates intracellular FZR1 protein levels. Upregulated FZR1 attenuates mitochondrial antiviral-signaling protein (MAVS) binding to 6-Phosphofructo-2-Kinase/Fructose-2, 6-Biphosphatase 3, a glycolytic rate-limiting enzyme, thereby promoting MAVS aggregation. Furthermore, FZR1 facilitates tumor necrosis factor receptor-associated factor 3/6 (TRAF3/6) autoubiquitination independently of the anaphase-promoting complex/cyclosome, subsequently activating interferon regulatory factor 3 and P65 of nuclear factor κB to drive the production of IFN-I and proinflammatory cytokines. Consequently, FZR1 deficiency impairs antiviral responses and increases viral titer in vitro and in vivo. Pharmacological inhibition of FZR1 significantly attenuates MAVS activation and TRAF3/6 ubiquitination, thereby abolishing FZR1-mediated antiviral immunity both in vitro and in vivo. Collectively, these findings reveal a molecular mechanism by which m 6 A modification of FZR1 activates the MAVS–TRAF3/6 signaling axis to potentiate IFN-I-dependent antiviral innate immunity.